STABILITY AND PREFERENCE OF RED PALM OIL EMULSION PREPARED WITH VARIOUS CONCENTRATION OF TWEEN 80 - Nurhayati Nurhayati; Budiyanto Budiyanto (Jurnal Agroindustri, 2016)
Red palm oil, rich in carotenoids (?, ?, ? - carotene and tocopherol and tekotrienol), has been shown to have benefit properties to human health. The aims of the study are : 1) to obtain the stability of red palm oil emulsions; 2) to determine the viscosity in red palm oil emulsion, 3) to determine the level of consumer preferences. Three levels of tween 80 emulsion concentrations (0,5%; 1%; and 1,5%) were employed to produce red palm oil emulsions. The stability, viscosity, and the preference of the emulsions were compared with commercial scot emulsion. The results showed that the level the stability of red palm oil emulsion prepared using Tween 80 1% and 0.5% CMC stable for 22.27 hours, while Scott's emulsion over 4 weeks. In addition, Red palm oil emulsion prepared with 1.5% Tween 80 and 0.5% CMC had viscosity of 16.6 cP , similar to viscosity of Scott's emulsion of 18.7 cP. The consumer prefered the color and the flavor of the red palm oil emulsion prepared with Tween 80 1% and 0.5% CMC compared to that of two other treatments.